Protocol for direct vaginal cytology of laboratory rats - Tammy Fernández Romero; Gipsis Suárez Román; Sonia Clapés Hernández (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Direct vaginal cytology is a widely used method for the evaluation of the estrous cycle of laboratory rats, but the information about the procedures and interpretation of results is dispersed through literature, making its use difficult in investigations on reproduction. Objective: To propose a protocol for performing direct vaginal cytology of laboratory rats as well as for the interpretation of the results. Material and methods: The information obtained from literature and the experience of 10 years of investigation on reproduction in 250 female Wistar rats were combined following the established ethical principles. The procedures for obtaining samples by vaginal washing and by observation and analysis in humid state with light microscope equipped with digital camera were described. Results: The main types of cells present in the vaginal washing and the characteristics that allow us to identify each phase or transitional phases of the estrus cycle are described. Aspects to take into consideration in the interpretation of the results, which include the association between hormonal changes, the cares in the obtaining of the sample and the influence of environmental factors, are discussed. Representative images and figures are included to illustrate the text. Conclusions: The work consists of a study protocol of the estrus cycle of laboratory rats by direct vaginal cytology. It provides noninvasive, simple and cost-reducing procedures as well as essential knowledge for the interpretation of results which integrate a very useful guideline for experimental investigations on reproduction.